2021
DOI: 10.3390/pharmaceutics13010065
|View full text |Cite
|
Sign up to set email alerts
|

New Protein-Coated Silver Nanoparticles: Characterization, Antitumor and Amoebicidal Activity, Antiproliferative Selectivity, Genotoxicity, and Biocompatibility Evaluation

Abstract: Nanomaterials quickly evolve to produce safe and effective biomedical alternatives, mainly silver nanoparticles (AgNPs). The AgNPs’ antibacterial, antiviral, and antitumor properties convert them into a recurrent scaffold to produce new treatment options. This work reported the full characterization of a highly biocompatible protein-coated AgNPs formulation and their selective antitumor and amoebicidal activity. The protein-coated AgNPs formulation exhibits a half-inhibitory concentration (IC50) = 19.7 µM (2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Interestingly, even with the significant accumulation in the tissue, minimal damage was observed. The lack of damage could be attributed to the considerable amount of coating agent, enhanced by its high clearance rate, as we have shown in previous works [18,21,[64][65][66][67]. These features definitely contribute to the wide therapeutic window found for the five formulations assessed in this work.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Interestingly, even with the significant accumulation in the tissue, minimal damage was observed. The lack of damage could be attributed to the considerable amount of coating agent, enhanced by its high clearance rate, as we have shown in previous works [18,21,[64][65][66][67]. These features definitely contribute to the wide therapeutic window found for the five formulations assessed in this work.…”
Section: Discussionsupporting
confidence: 68%
“…However, we recently showed that the coating agent selection is not the only thing you need to worry about. The metallic content/coating agent ratio plays a significant role in the cytotoxic and genotoxic response of AgNPs [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work investigated the genotoxic potential of the commercially available Argovit™ AgNP formulation on BALB/c mice. This formulation has shown remarkable results as an antiviral [ 13 , 14 , 34 , 35 ], antimicrobial [ 36 , 37 , 38 , 39 , 40 ], and growth promoter of commercially relevant crops [ 41 , 42 ] with very low cytotoxic [ 17 ] and phytotoxic [ 18 ] damages. For the purposes of the study, we orally administered a daily dose of 6 mg/kg of AgNPs for three consecutive days and continued the observation for five more days.…”
Section: Discussionmentioning
confidence: 99%
“…A new question arises: do AgNPs serve as adjuvants for CP? The antiproliferative activity of Argovit™ AgNPs against several human tumor cell lines has been previously reported [ 40 , 61 ]. Therefore, this suggests that the combination of AgNPs + CP could behave as a potent antiproliferative agent, significantly decreasing the genotoxic damage induced by CP potentially attributed to the action of AgNPs.…”
Section: Discussionmentioning
confidence: 99%